Amateur Theatre at the Early Modern Inns of Court? The Implications of a Performance Copy of Jonson’s 1640 Folio - Harrison, Tom; Loxley, James (Early Theatre, 2023)
This article discusses a recently rediscovered copy of Ben Jonson's 1640 Workes that contains seventeenth-century annotations to Epicene that suggest preparations for performance. We trace the folio copy’s provenance with the Powell family in Nanteos, Wales, and consider the possibility that it may have been annotated when in the possession of Sir Thomas Powell, a lawyer and judge who spent much of his life in London. We argue that the annotated play-text can be connected to four other playbooks by William Shakespeare and James Shirley that have been previously associated with seventeenth-century amateur theatricals, and that the new evidence provided by the Jonson text points plausibly to a practice of amateur performance at and around Gray's Inn in the middle of the century.